Alexithymia, traumatic stress symptoms and burnout in female healthcare professionals. Issue 4 (April 2020) - Riethof, Norbert; Bob, Petr; Laker, Matthew; Zmolikova, Jana; Jiraskova, Terezie; Raboch, Jiri
Objective: The burnout syndrome represents a defence mechanism against stress and includes stages with decreased ability to experience feelings and emotional states. This finding suggests that burnout might be closely linked to emotional 'blindness' as a defence mechanism against negative and overwhelming emotions known as alexithymia. The aim of this study is to examine the relationships between burnout syndrome, alexithymia, depression and traumatic stress symptoms in healthcare professionals. Methods: This empirical study assessed female healthcare professionals who work with a population of patients with diabetes, utilizing the Maslach Burnout Inventory (MBI-HSSMP), Burnout Measure (BM), Toronto Alexithymia Scale (TAS-20), Beck Depression Inventory (BDI-II) and Traumatic Stress Checklist (TSC-40). Data were analysed using Spearman's correlation coefficient. Results: A total of 114 female participants were included (age range, 31–60 years; mean age, 46.62 ± 8.71 years). Statistically significant associations were found between burnout syndrome (BM scores) and alexithymia (TAS-20) ( r  = 0.41), and between BM scores and traumatic stress (TSC-40; r  = 0.63). The MBI-HSSMP emotional exhaustion subscale also correlated with alexithymia (TAS-20) ( r  = 0.37). Conclusion: Findings of this study suggest that alexithymia and traumatic stress are related to burnout symptoms. This dynamic may be potentially useful for detecting and preventing burnout syndrome.